2014
DOI: 10.1021/cs501211h
|View full text |Cite
|
Sign up to set email alerts
|

Single and Multiple Doping in Graphene Quantum Dots: Unraveling the Origin of Selectivity in the Oxygen Reduction Reaction

Abstract: Singly and multiply doped graphene oxide quantum dots have been synthesized by a simple electrochemical method using water as solvent. The obtained materials have been characterized by photoemission spectroscopy and scanning tunneling microscopy, in order to get a detailed picture of their chemical and structural properties. The electrochemical activity toward the oxygen reduction reaction of the doped graphene oxide quantum dots has been investigated by cyclic voltammetry and rotating disk electrode measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
138
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(148 citation statements)
references
References 103 publications
10
138
0
Order By: Relevance
“…They also observed that the −COOH group is comparatively difficult to remove than other oxygenated groups. 43,44 As many previous reports have reported an interesting fact, however, the list amount of −COOH group containing rGO showed better ORR activity, 18,[45][46][47] because it improves the edge of rGO which facile to the charge polarization of edge carbon atoms. 4 In this regards, the highquality and high-purity rGO production by L-ascorbic acid (AA) can be the harmless and easy approaches with much reduction of −COOH group from GO edge 48,49 and this is first time we have applied AA reduced AgNCs anchored rGO (AgNCs/rGO) for ORR catalysis.…”
mentioning
confidence: 90%
“…They also observed that the −COOH group is comparatively difficult to remove than other oxygenated groups. 43,44 As many previous reports have reported an interesting fact, however, the list amount of −COOH group containing rGO showed better ORR activity, 18,[45][46][47] because it improves the edge of rGO which facile to the charge polarization of edge carbon atoms. 4 In this regards, the highquality and high-purity rGO production by L-ascorbic acid (AA) can be the harmless and easy approaches with much reduction of −COOH group from GO edge 48,49 and this is first time we have applied AA reduced AgNCs anchored rGO (AgNCs/rGO) for ORR catalysis.…”
mentioning
confidence: 90%
“…an increase in the production of hydrogen peroxide during the ORR on N-doped and non-reduced graphene oxide quantum dots [36], N-doped graphenes [37] and graphiticbased materials (highly oriented pyrolytic graphite and glassy carbon) with quinones, anthraquinones and hydroquinones as surface functional groups [38,39]. This behavior is also reflected when calculating the number of electrons transferred during the reaction (see blue lines in Figure 4).…”
Section: Oxygen Reduction Reaction (Orr) On the Synthesized Catalystsmentioning
confidence: 97%
“…Generally, the approaches can be divided into two groups: top-down and bottom-up methods. In the top-down methods, GQDs are usually synthesized through the cleavage of relatively large bulk precursors, such as graphite [53][54][55], carbon black [56][57][58], coal [59][60][61], metal-organic framework (MOF) [40], 3D graphene [62], graphene oxide (GO) [63][64][65][66][67], carbon nanotubes [68][69][70], carbon fiber [53,[71][72][73] and C 60 [74,75] into small pieces of graphene sheets by chemical oxidation etching [76][77][78][79][80][81], electrochemical exfoliation [65,[82][83][84][85], Li/K intercalation [86,87], hydrothermal/solvothermal treatment [88][89][90][91][92][93][94], microwave irradiation [95...…”
Section: Synthesis and Optical Property Of Gqdsmentioning
confidence: 99%
“…Furthermore, doping and/or surface passivation are effective methods to modulate the electronic density of bulk semiconductor materials and to tune their optical and electrical properties. So, dicyandiamide (DCD) [105,106,112], ammonium hydroxide [77,89,91,93,114,115,[129][130][131][132], diethylenetriamine (DETA) [133], urea [107], ethylenediamine (EDA) [111], dimethylformamide (DMF) [38,134] and hydrazine hydrate [123] are chosen as the nitrogen source for doping or modifying GQDs to synthesize nitrogen-functionalized GQDs, while 1,4-phenylene bis(boronic acid) [65], boron oxide (B 2 O 3 ) [76] and Na 2 B 4 O 7 [135] are employed as boron sources to prepare boron-functionalized GQDs. Also, nitrogen and sulfur co-functionalized GQDs are successfully obtained using nitrogen and sulfur containing compounds of 1-methyl-1-propylpiperidinium bis(trifluoromethylsulfonyl) imide [68], polythiophene [136] and thiourea [110].…”
Section: Synthesis and Optical Property Of Gqdsmentioning
confidence: 99%